FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN PERSALINAN PREMATUR DI RSIA STELLA MARIS MEDAN TAHUN 2022 - Lenny Sijabat; Idona Gokmarina; Firma Simatupang; Siska Suci Triana Ginting; Vidya Silvyani Audry (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background: Preterm/preterm delivery is still a problem in the world including Indonesia, related to prevalence, morbidity and perinatal mortality which is the main cause of infant death and the second cause of death after pneumonia in children under five years of age. This study aims to determine the factors that influence the incidence of preterm labor at Rsia Stella Maris Medan in 2022. Method: This type of research is a descriptive study, with a cross-sectional design. Sampling was carried out systematically (systematic random sampling), where the sample in this study was 64 respondents. Data collection techniques using a questionnaire sheet. The bivariate analysis technique uses the che square test. Results: the results are almost half of the birth events with ages <20->35 years as many as 40 respondents (59.4%) almost half of the birth events with parity ≥5 times as many as 38 respondents (32.9%), most of the birth events with Ever experienced premature labor as many as 35 respondents (54.7%), almost half of those with premature rupture of membranes were 34 (53.1%), most of the incidents of childbirth with placenta previa were pregnant women not with placenta previa as many as 44 respondents (68.8%), most of the incidents of childbirth with pregnant women who experienced preeclampsia/eclampsia were (56.2%) and most of the deliveries were with twin pregnancies for pregnant women with single pregnancies as many as 36 respondents (56.2%). Conclusion: That there is a relationship between age, parity, history of preterm labor, PROM, Placenta Previa, Preeclampsia/Eclampsia, Twin Pregnancies Affecting Premature Labor at Rsia Stella Maris Medan in 2022